TRANSFORMATION OF THE NURSES LEARNING FOR COMPETENCE DEVELOPMENT AND IMPROVEMENT - Jankovska, Livija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Transformation of the learning environment is an important factor for the innovation of the educational process. Contemporary educational paradigm requires new approaches which promote complicated and multidisciplinary competencies. Professional development of nurses depends on acquisition of new and more complicated cognitive, psychomotor and affective competencies to meet the contemporary needs of the medical care. Analyses of the empirical research results reveals that students evaluate their professional practical skills not very high that proves the need of  closer connection of the theory and corresponding practice in order students can acquire high quality integrative competences, which prepare for professional, social and personal challenges. Affective competences are playing major role in modern health care but the teachers’ questionnaire data show that students underestimate attitudes for their professional life. Thus, attitude forming is an important task of nurses’ education. One more factor is to prepare nurses for digital changes in Latvia medical system that requires integrative solutions for the multifunctional, active, information technology and practice oriented learning and teaching. Content and structure of new didactic models should promote interactive, technology improved and work-based learning process in order to provide sustainable education.